Emergence of (hydro)persulfides as suppressors of lipid peroxidation and ferroptotic cell death - Wu, Zijun; Barayeu, Uladzimir; Schilling, Danny; Dick, Tobias P.; Pratt, Derek A. (Current opinion in chemical biology, 2023)
Recognition of the prevalence of hydropersulfides (RSSH) and characterization of their enhanced two-electron reactivity relative to thiols have led to their implication in maintaining cellular redox homeostasis, in addition to other potential roles. Recent attention on the one-electron reactivity of RSSH has uncovered their potent radical-trapping antioxidant activity, which enables them to inhibit phospholipid peroxidation and associated cell death by ferroptosis. Herein, we briefly review key aspects of the reactivity and underlying physicochemical properties of RSSH. We emphasize their reactivity to radicals - particularly lipid peroxyl radicals that propagate the lipid peroxidation chain reaction - and the recent recognition that this results in ferroptosis suppression. We highlight open questions related to recent developments in this area and, given that all living organisms possess the ability to synthesize persulfides endogenously, suggest they may be primordial radical scavengers that occurred early in evolution and still play a role today.